Consumer Perceptions of Price, Quality, and Value: A Means-End Model and Synthesis of Evidence - Zeithaml, Valarie A. (Journal of Marketing, 1988)
Evidence from past research and insights from an exploratory investigation are combined in a conceptual model that defines and relates price, perceived quality, and perceived value. Propositions about the concepts and their relationships are presented, then supported with evidence from the literature. Discussion centers on directions for research and implications for managing price, quality, and value.